Does Photomineralization of Dissolved Organics Matter in Temperate Rivers?. Issue 7 (27th July 2021) - Maavara, Taylor; Logozzo, Laura; Stubbins, Aron; Aho, Kelly; Brinkerhoff, Craig; Hosen, Jacob; Raymond, Peter
Abstract: Sunlight can oxidize dissolved organic carbon (DOC) to dissolved inorganic carbon (DIC) in freshwaters. The importance of complete photooxidation, or photomineralization, as a sink for DOC remains unclear in temperate rivers, as most estimates are restricted to lakes, high latitude rivers, and coastal river plumes. In this study, we construct a model representing over 75, 000 river reaches in the Connecticut River Watershed (CRW), USA, to calculate spectrally resolved photomineralization. We test the hypothesis that photomineralization is a negligible DOC sink across all reaches and flow conditions relative to DOC fluxes. Our model quantifies reaction rates and transport drivers within the river reaches for the ranges of flow conditions, incoming solar irradiance, and canopy cover shading observed throughout the year. Our model predicts average daily areal photomineralization rates ranging from 1.16 mg‐C m −2  day −1 in low flow river reaches in the winter, to 18.33 mg‐C m −2  day −1 in high flow river reaches during the summer. Even for high photomineralization fluxes, corresponding photomineralization uptake velocities are typically at least an order of magnitude smaller than those reported for other instream processes. We calculate DOC elimination by photomineralization relative to DOC fluxes through individual stream reaches as well as the entire riverine portion of the CRW. We find that relative photomineralization fluxes are highest in summer drought conditions in low order streams. In median flows and mean light intensities, for an average watershed travel distance, 3%–5% of the DOC fluxes are eliminated, indicating that photomineralization is a minor DOC sink in temperate rivers. Plain Language Summary: Rivers are an important part of the carbon cycle, moving carbon compounds from land to the ocean. Within rivers, dissolved organic carbon molecules can be broken down into inorganic carbon molecules, including the greenhouse gas carbon dioxide. Sunlight shining into rivers can cause these organic molecules to break down in a process called photomineralization, but it is not clear if this process is important compared to the total amount of organic carbon that travels through rivers every day. In this paper, we build a model for the river sections of temperate Connecticut River Watershed, which calculates photomineralization for possible river flow conditions, dissolved organic carbon concentrations, and seasons, and compares the size of the sunlight‐driven breakdown of dissolved organic carbon to the amount of dissolved organic carbon in the river. This is the first model that puts photomineralization rates in the context of a flowing temperate river network. We show that compared with the dissolved organic carbon amounts present in the river at any time of the year or any flow conditions, photomineralization is essentially an unimportant process, removing on average 3%–5% of the dissolved organic carbon through an average watershed river route. Key Points: We build a model calculating reaction and transport drivers for photomineralization in 75, 000 temperate river reaches Photomineralization is a negligible dissolved organic carbon (DOC) sink relative to DOC fluxes DOC elimination by photomineralization in temperate rivers is limited by short water residence times and canopy cover